(untitled) (Research, Society and Development, 2022)
Exploratory qualitative research report, presenting the results of the application of a questionnaire to identify, in the experience of women and men between 20 and 54 years old, 4 symptoms associated with adaptive, social and panic anxiety: fatigue; difficulty concentrating; fear and intrusive/catastrophic thoughts for further treatment. The questionnaire was answered by 21 women and 8 men, living in a capital city in the North Region. Open and closed questions focused on the onset of anxiety; social situations and anxious people; relationship with food; physical activity; psychiatric treatment, self-support, customary personal strategies for coping with anxiety. The profile of the participants includes complete and incomplete higher education. In the analyses, we organized 4 sections: identification; general health: presence/absence of skin and/or respiratory allergies; hypertension and cholesterol; food; characterization of anxiety. We conclude that anxiety is one of the sources of psychological suffering that affects men and women, with the social factor in the experiences of some having a highlighted severity, disconnected from the context of what they do at university and at work; stressful situations, have different weights and feelings, which demonstrates the potency of the context in the impacts on health. Some men reported non-drug coping strategies for anxiety symptoms; none do psychotherapy, which reiterates the importance of interdisciplinary programs, including phytotherapy so that the treatment of anxiety is not only psychiatric.